Effect of lignin modification on properties of kenaf core fiber reinforced poly(butylene succinate) biocomposites - Ahmad Saffian, Harmaen; Kim, Hyun Joong; Md. Tahir, Paridah; Ibrahim, Nor Azowa; Lee, Seng Hua; Lee, Ching Hao (MDPI, 2019)
In this study, the effects of lignin modification on the properties of kenaf core fiber reinforced poly(butylene succinate) biocomposites were examined. A weight percent gain (WPG) value of 30.21% was recorded after the lignin were modified with maleic anhydride. Lower mechanical properties were observed for lignin composites because of incompatible bonding between the hydrophobic matrix and the hydrophilic lignin. Modified lignin (ML) was found to have a better interfacial bonding, since maleic anhydrides remove most of the hydrophilic hydrogen bonding (this was proven by a Fourier-transform infrared (FTIR) spectrometer—a reduction of broadband near 3400 cm−1, corresponding to the –OH stretching vibration of hydroxyl groups for the ML samples). On the other hand, ML was found to have a slightly lower glass transition temperature, Tg, since reactions with maleic anhydride destroy most of the intra- and inter-molecular hydrogen bonds, resulting in a softer structure at elevated temperatures. The addition of kraft lignin was found to increase the thermal stability of the PBS polymer composites, while modified kraft lignin showed higher thermal stability than pure kraft lignin and possessed delayed onset thermal degradation temperature.